(untitled) (Human Factors in Design, 2025)
Teamwork requires assertive communication to increase the synergy between the people involved. Among the methods that can be used to improve communication is gamification, which using points, badges, rankings, and other elements can lead to increased motivation for actions to improve communication. This paper seeks to explore and identify elements of gamification that can improve teamwork using more assertive communication among team members who are developing game projects in an undergraduate course. The work uses pre-testing and testing to identify common problems in design activity and tests that seek to identify the potential use of gamification in academic environments in design activity.